Clinical Effect of Apatinib Mesylate Tablets Combined with Paclitaxel Concurrent Radiotherapy and Chemotherapy in the First-Line Treatment of Locally Advanced Nasopharyngeal Carcinoma - Dechao Zhan; Zihong Chen; Donghong Yang; Jiyu Wen; Wanwan Liu (Emergency Medicine International)
Objective. To explore the clinical efficacy and safety of apatinib combined with paclitaxel in the first-line treatment of locally advanced nasopharyngeal carcinoma. Methods. From March 2016 to June 2018, 114 patients with locally advanced nasopharyngeal carcinoma who received first-line treatment in our hospital were selected as the patient group, and those who received apatinib combined with paclitaxel concurrent radiotherapy and chemotherapy were selected as the research group (n = 54), while those who received paclitaxel concurrent radiotherapy and chemotherapy were selected as the control group (n = 60). Sixty healthy individuals in our hospital were recruited in the same period as the healthy group. The clinical effective rate, adverse reactions, 2-year overall survival rate (OS), 2-year progression-free survival rate (PFS), and quality of life were compared between the two groups, and the expression of miR-655 in the serum of each group was tested by RT-qPCR. Results. The total clinical effective rate of the research group was higher than that of the control group, and the 2-year OS and PFS of the research group were also higher than those of the control group (P<0.05). Both groups of patients could tolerate the treatment, but the incidence of hypertension and proteinuria in the research group was higher than that in the control group (P<0.05). The expression of miR-655 in the serum of patients was lower than that of the healthy group (P<0.05). After treatment, miR-655 in serum increased in both the groups and miR-655 in the research group was higher than that in the control group (P<0.05). The 2-year survival rate of OS and PFS in patients with low expression of miR-655 was significantly lower than that in patients with high expression of miR-655 (P<0.05). Conclusion. Apatinib combined with paclitaxel concurrent radiotherapy and chemotherapy is effective and well-tolerated in the treatment of locally advanced nasopharyngeal carcinoma, which improves the quality of life of patients and can be popularized in clinical practice. In addition, the increase of miR-655 may be a target for treating nasopharyngeal carcinoma.